Relation of Food Sources of Fructose Containing Sugars With Incident Obesity Outcomes: A Systematic Review and Meta-Analysis of Prospective Cohort Studies. (7th June 2021) - Zurbau, Andreea; Mejia, Sonia Blanco; Khan, Tauseef; Kavanagh, Meaghan; Glenn, Andrea; Au-Yeung, Fei; Kendall, Cyril; Sievenpiper, John
Abstract: Objectives: Sugars have been implicated in the epidemic of obesity. It is unclear whether food sources of fructose-containing sugars other than sugar-sweetened beverages (SSBs) are associated with increased risk of obesity. To assess the evidence of the relation of food sources of fructose-containing sugars with incident overweight or obesity, we undertook a systematic review and meta-analysis of prospective cohort studies. Methods: We searched MEDLINE, EMBASE and Cochrane Library through Aug 2019. We included prospective cohort studies of ≥1 year. Two reviewers extracted data and assessed the risk of bias. The primary outcome was incident overweight/obesity. Data were pooled using generic-inverse variance method (random effects) and expressed as relative risks (RR) for incident outcomes and ß-coefficients for WC with 95% confidence intervals (CI). GRADE assessed the certainty of evidence Results: We included 12 and 8 prospective cohorts involving 181, 295 adults and 31, 717 children, respectively. Four food sources of fructose-containing sugars were identified: SSBs, 100% fruit juice, fruit and yogurt. There was no data available in children for yogurt or WC. SSBs were associated with increased incident overweight/obesity in children (RR, 1.22 [95% CI, 1.03 to 1.44] but not in adults and increased incident abdominal obesity in both children (3.78 [1.08 to 13.25]) and adults (1.51 [1.11 to 2.06]), but there was no association with change in WC in adults. Fruit juice was associated with increased incident overweight/obesity in children (1.28 [1.07 to 1.53]) but not in adults, and there was no association with incident abdominal obesity in either children or adults or WC in adults. Fruit was associated with decreased incident overweight/obesity (0.87 [0.82 to 0.92]) and decreased WC (ß, −0.23 cm [−0.33 to −0.13]) in adults. Yogurt was associated with decreased incident abdominal obesity (0.65 [0.47 to 0.90]) in adults with no data available on WC. The certainty of the evidence was graded as "very low" to "moderate". Conclusions: Current evidence indicates that the relation between fructose-containing sugars and obesity outcomes differs by food sources. More research of more food sources of sugars is needed to improve our certainty in the evidence. (ClinicalTrials.gov, NCT02558920) Funding Sources: ASN, Diabetes Canada, Banting and Best Diabetes Centre.